Synthesis and X-Ray Structural Investigation of N,N’-1,6-diaminohexane bis-Salicylaldehyde - SHEIKHSHOAIE, IRAN (Asian Journal of Chemistry, 2010)
A symmetrical potentially tetradentate N2O2 Schiff base N,N'-1,6-diaminohexane bis-salicylaldehyde (H2L), (2-OH) C6H4-CH = N(CH2)6 N = CH-C6H4 (2-OH) was synthesized and characterized by spectroscopic methods (FT-IR, 1H NMR, 13C NMR) and C, H, N analysis. The tetradentate Schiff base was derived from the condensation reaction between 0.001 mol of 1,6-diaminohexane with 0.002 mol salicylaldehyde in ethanol as a solution. In the other part of this work the geometry of (H2L) Schiff base compound was fully optimized in the gas phase by AM1 semi-empirical method. Mulliken population study shows two nitrogen atoms and two oxygen atoms are the coordination sites for binding to the metal ions.